Distal femur versus humeral or tibial IO, access in adult out of hospital cardiac resuscitation. (January 2022) - Rayas, Emmanuel Giovanni; Winckler, Christopher; Bolleter, Scotty; Stringfellow, Michael; Miramontes, David; Shumaker, Joi; Lewis, Alan; Wampler, David
Abstract: Background: Intraosseous (IO) vascular access is a well-established method for fluid and drug administration in the critically ill. The Food and Drug Administration has approved adult IO access at the proximal humerus, proximal tibia, and the sternum; all three sites have significant limitations. The Distal Femur is away from the chest, with high flow rates. The objective of this study was to evaluate the distal femur site during resuscitation of adult out-of-hospital cardiac arrest. Methods: A retrospective analysis of adult out of hospital cardiac arrest patients treated by the San Antonio Fire Department. IO access was obtained by first-responders (paramedics or EMT-basic) or EMS paramedics. All resuscitation attempts from 2017 to 2018 data were analyzed. The protocol did not dictate the preference of IO site. The primary measure: number of OHCA patients in each subgroup: IO femur, IO humerus, IO tibia. Secondary measures: paramedic or basic operator, dislodgement rate, and total fluid infused. Results: There were 2, 198 patients meeting inclusion criteria: 888 femur, 696 humerus, 432 tibia. Distal femur increased 2.5 times in the 2018 cohort compared to the 2017 cohort, with a corresponding decrease in humerus (factor of 0.29). Proximal tibia remained unchanged. Dislodgement rates and total infusion (ml) remained unchanged. Conclusions: The distal femur IO was feasible and associated with similar measured performance parameters as other IO sites in adult OHCA for both advanced and basic life support personnel.